Dominant Risk Factors in Stroke Cases at A Young Age: A Systematic Review And Meta Analysis - Adriani, Rita Benya; Sulistyowati, Dwi; Hapsari, Happy Indri (Sekolah Tinggi Ilmu Kesehatan Kendal, 2025)
Stroke in young adults is a significant global health concern, with multiple risk factors contributing to its incidence. Identifying these risk factors is crucial for prevention and early intervention. However, limited studies focus on young stroke patients, making a systematic review and meta-analysis necessary to synthesize available evidence. Objective: This study aims to systematically review and analyze the association between hypertension, smoking, alcohol consumption, and waist-to-hip ratio with the incidence of stroke in young adults through a meta-analysis of observational studies. Method: A systematic review and meta-analysis were conducted following PRISMA guidelines. Literature searches were performed in Google Scholar, ProQuest, and PubMed from January 1, 1990 up to January 31, 2024, using predefined keywords. Eligible studies included case-control studies employing logistic regression analysis. Quality assessment was conducted using the Newcastle-Ottawa Scale. Odds ratios (OR) with 95% confidence intervals (CI) were calculated using a random-effects or fixed-effects model depending on heterogeneity levels. Statistical analyses were performed using Review Manager (RevMan) software. Results: Three studies were included in the meta-analysis. Hypertension (OR 4.24, 95% CI: 2.12–8.48, p=0.0001, I²=69%) and alcohol consumption (OR 6.29, 95% CI: 2.27–17.45, p=0.0004, I²=0%) were significantly associated with stroke. Smoking also showed a significant association (OR 2.04, 95% CI: 1.40–2.97, p=0.0002, I²=0%). However, waist-to-hip ratio was not significantly associated (OR 3.64, 95% CI: 0.57–23.10, p=0.17, I²=76%). Conclusions: Hypertension, alcohol consumption, and smoking are significant risk factors for stroke in young adults, while waist-to-hip ratio shows no clear association. These findings emphasize the importance of targeted preventive strategies to reduce stroke incidence in younger populations.